Relaxation of microparticles exposed to hydrodynamic forces in microfluidic conduits - Janča, Josef; Halabalová, Věra; Polášek, Vladimír; Vašina, Martin; Menshikova, Anastasia Yu (Analytical and bioanalytical chemistry, 2011)
The behavior of microparticles exposed to gravitational and lift forces and to the velocity gradient in flow velocity profile formed in microfluidic conduits is studied from the viewpoint of the transient period (the relaxation) between the moment at which a particle starts to be transported by the hydrodynamic flow and the time at which it reaches an equilibrium position, characterized by a balance of all active forces. The theoretical model allowing the calculation of the relaxation time is proposed. The numerical calculus based on the proposed model is compared with the experimental data obtained under different experimental conditions, namely, for different lengths of microfluidic channels, different average linear velocities of the carrier liquid, and different sizes and densities of the particles used in the study. The results are important for the optimization of microfluidic separation units such as microthermal field-flow fractionation channels in which the separation or manipulation of the microparticles of various origin, synthetic, natural, biological, etc., is performed under similar experimental conditions but by applying an additional thermodynamic force.
Keywords: Hydrodynamics; hydrodynamika; Microfluidic Analytical Techniques; mikrofluidní analytické techniky; Particle Size; velikost částic